2014
DOI: 10.1111/jdv.12691
|View full text |Cite
|
Sign up to set email alerts
|

A possible relationship of human leucocyte antigens with psoriasis vulgaris and geographic tongue

Abstract: HLA-B*58 was associated with GT and HLA-B*57 was possibly associated with psoriasis. This suggested that some GT cases may represent true oral psoriasis and some may represent only GT. Therefore, it is necessary to make this distinction and increase our sample size to improve the correct diagnosis and treatment of these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…Similar to GT, psoriasis is a dermal, inflammatory, genetic, and immunological disease with much clinical importance . Studies show that GT is the most common oral lesion associated with psoriasis based on the microscopic similarity between these conditions and the presence of a common genetic marker, HLA‐Cw6 . Some authors have questioned the diagnosis of GT as oral psoriasis since there are some patients who present with GT but not psoriasis …”
Section: Discussionmentioning
confidence: 99%
“…Similar to GT, psoriasis is a dermal, inflammatory, genetic, and immunological disease with much clinical importance . Studies show that GT is the most common oral lesion associated with psoriasis based on the microscopic similarity between these conditions and the presence of a common genetic marker, HLA‐Cw6 . Some authors have questioned the diagnosis of GT as oral psoriasis since there are some patients who present with GT but not psoriasis …”
Section: Discussionmentioning
confidence: 99%
“…19,54 The serologic equivalent for these alleles (HLA-B*57 e -B*58) is the HLA-B17 antigen. Possibly this may explain the association between psoriasis and geographic tongue, respectively, with these alleles.…”
Section: Histopathologic and Immunogenetic Similarities Between Geogrmentioning
confidence: 99%
“…Possibly this may explain the association between psoriasis and geographic tongue, respectively, with these alleles. 54 …”
Section: Histopathologic and Immunogenetic Similarities Between Geogrmentioning
confidence: 99%
“…Several studies have demonstrated associations between BMG and psoriasis, suggesting that BMG is a form of oral psoriasis (6)(7)(8). Emotional stress and other environmental factors may be responsible for different types of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…While most epidemiological studies report a mean prevalence of 0.78 to 6.8% (2)(3)(4)(5), the etiology and pathogenesis of BMG remain obscure. In addition to psoriasis, it has been implied that BMG is an oral manifestation of this cutaneous disease (6)(7)(8)(9), and several authors have suggested the presence of a relationship between psoriasis and BMG, fissured tongue, and geographic stomatitis (6)(7)(8)(9). Emotional stress has been reported to be a triggering factor in these conditions.…”
Section: Introductionmentioning
confidence: 99%